Evaluasi Perilaku Penggunaan Obat Sebelum Pasien Terdiagnosa Penyakit Ginjal Kronis Di Rsud Soesilo Kabupaten Tegal Dan Rsud Kardinah Kota Tegal Periode Januari – Agustus 2016 - khusny kamal (Parapemikir : Jurnal Ilmiah Farmasi, 2020)
The number of people with Chronic Kidney Disease (CKD) continues to increase and is considered as one of the health problems that can develop into an epidemic. Increasing the use of over the counter (OTC) products, the use of traditional medicines mixed with medicinal chemicals, the use of hard drugs freely brings concerns and concerns about the quality, effectiveness, safety of the products used. This study aims to look at patient distribution, drug use behavior before being diagnosed with CKD in Soeselo Regional Hospital and Kardinah Regional Hospital. The method used in this study is cross sectional by giving prospective questionnaires to patients who fall into the inclusion criteria. The sample used was chronic kidney patients undergoing treatment at Soeselo Regional Hospital as many as 56 respondents and 138 respondents at the Kardinah Regional Hospital in the period January 2016 - August 2016. Data were analyzed statistically using the chi square test to see the proportion of CKD distribution and behavior of drug use of patients in the Regional Hospital Soeselo with Kardinah Regional Hospital. Based on the results of the study, the demographic characteristics obtained male sex, age 50 years, the type of occupation with moderate physical activity is a high proportion in Kardinah Regional Hospital while the distribution of education level is the highest proportion in Soeselo Regional Hospital. the most widely used is pain reliever (42.6%), where there are significant behavioral differences in Soeselo Regional Hospital with Kardinah Regional Hospital on the behavior of using herbal medicine in racik at home and in the holding of herbal medicine where the proportion of usage in Kardinah Regional Hospital is much higher than in Soesilo Regional Hospital p-value (p 0.05) while the most widely used drugs or health supplements are herbal medicine packaging at home (22.6%) and no significant differences were found (p 0.05) for supplement use behavior health to maintain stamina and health in both hospitals.